2018
DOI: 10.1097/01.ccm.0000528475.97055.05
|View full text |Cite
|
Sign up to set email alerts
|

457: Delirium and Catatonia in Critically Ill Patients: The Decat Prospective Cohort Investigation

Abstract: Objective-Catatonia, a condition characterized by motor, behavioral and emotional changes, can occur during critical illness and appear as clinically similar to delirium, yet its management differs from delirium. Traditional criteria for medical catatonia preclude it's diagnosis in delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 22 publications
(27 reference statements)
1
33
0
1
Order By: Relevance
“…Delirious patients can be further characterized as hyperactive, hypoactive or mixed forms, based on abnormalities of psychomotor behavior 34 . Catatonia is now recognized to frequently co-occur with delirium in the context of general medical and critical illnesses [35][36][37][38] , however the clinical relevance of this co-occurrence remains unknown.…”
Section: Catatonia Is a Psychomotor Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Delirious patients can be further characterized as hyperactive, hypoactive or mixed forms, based on abnormalities of psychomotor behavior 34 . Catatonia is now recognized to frequently co-occur with delirium in the context of general medical and critical illnesses [35][36][37][38] , however the clinical relevance of this co-occurrence remains unknown.…”
Section: Catatonia Is a Psychomotor Syndromementioning
confidence: 99%
“…Catatonia is a frequent manifestation of many general medical conditions 64,[71][72][73] . Studies have suggested that perhaps as many as one third of patients with delirium secondary to a general medical condition will develop catatonia during their acute hospitalization 35,36 . Catatonia incidence ranged from 1•6% to 8•9% on medical services assessed by a psychiatry liaison service, with prevalence varying across age groups and associated medical conditions 74,75 .…”
Section: Nosology and Epidemiology Of Catatoniamentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] Some studies have suggested that catatonia due to medical illness can coexist with delirium in the ICU population at rates as high as 31%. [28]…”
Section: Clinical Featuresmentioning
confidence: 99%
“…As exemplified by the patients in this case series and explored in the discussion, there is possible increased risk of catatonia in COVID-19 patients. Additionally, a study of critically ill patients has shown that an increased number of signs of catatonia in a patient were associated with a greater likelihood of concurrent delirium [11]. The pathophysiology of COVID-19 and its consequences on the central nervous system (CNS) may provide an explanation for increased risk of the aforementioned neuropsychiatric findings.…”
mentioning
confidence: 99%